2018
DOI: 10.1155/2018/8101359
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-146a and miR-150 as Potential New Biomarkers for Hip Fracture-Induced Acute Lung Injury

Abstract: Background Acute lung injury (ALI) and subsequent pulmonary infection are the most severe and usually fatal complications for elderly hip fracture patients. It is necessary to find some biomarkers for early diagnosis and prognosis of it. Objective This study is aimed at examining the differential expression of miR-146a, miR-150, and cytokines (IL-6 and IL-10) between younger and elderly rats suffering from hip fracture and investigating the possible meaning of them in early diagnosis and prognosis of ALI after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Numerous studies have proven that miR-146a is closely related to inflammation (46)(47)(48). There is also considerable evidence that miR-146a is closely linked to lung diseases, including ARDS (49)(50)(51). The results of the target gene enrichment in the present study are consistent with previous results.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have proven that miR-146a is closely related to inflammation (46)(47)(48). There is also considerable evidence that miR-146a is closely linked to lung diseases, including ARDS (49)(50)(51). The results of the target gene enrichment in the present study are consistent with previous results.…”
Section: Discussionsupporting
confidence: 91%
“…Several biochemical markers of inflammation, such as levels of CRP, the soluble urokinase plasminogen activating receptor (suPAR) and ferritin, were found to be associated with 30-day mortality after hip fracture [ 15 ]. Hip fracture also led to significant systemic inflammation and acute lung injury in rat models, and the older rats suffered a more remarkable acute lung injury after hip fracture than the younger rats [ 37 ]. Although other study has found no such relationship between high inflammatory markers and 2-year mortality in hip fracture patients [ 38 ], most studies suggest that systemic inflammation may be related to the poor survival of hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Such screening has eventually identified three miRNAs (miR-30b, miR-146a and miR-190b) negatively regulating lung tumorigenesis. Previous studies have established the functional link between miR-146a and miR-190b and lung cancer, indicating that these two miRNAs might serve as diagnostic biomarkers [ 10 , 35 , 36 ]. The miR-190b is previously shown to be up-regulated in ERα-positive breast tumors compared to ERα-negative breast tumors [ 37 ].…”
Section: Discussionmentioning
confidence: 99%